REGULATORY APPROACHES ON ADVANCED SAFE USE OF NEW TECHNOLOGY LIGHT SOURCES IN AIR TRANSPORT (Научный вестник МГТУ ГА)
The article deals with the problems of advanced safe use of new technology light sources for air transport. New proposals for the use of point light-emitting diodes (LEDs) in aircraft cabins are given. The advantages of energy efficiency of LEDs and production costs are emphasized. The results of the study on the effect of LED electronic lighting system on human vision and health are analyzed. The requirements of international and domestic regulatory documents on the use of new technology light sources and risk regulation of light-biological danger are analyzed. Recommendations for practical application of light sources for aircraft cabin lighting are given.